(untitled) (Journal of Asian Development Studies, 2018)
The purpose of this study is to find out the key determinants of Foreign direct investment (FDI) in Pakistan in long run and short run time period. For this purpose, Co-integration approach and Error correction model (ECM) is used covering the time period 1973 to 2011. This study considers the Gross Domestic Product, Consumer Price Index, Political Instability, Exchange rate and Population. Augmented dickey fuller (ADF) has used to check the stationarity level of the variables in the model and found that all variables have the I(1) integrated order. All variables are found statistically significant in long run and concluded that Gross domestic product (GDP) in Pakistan is the most significant predictor of the FDI, followed by in order of importance the Political Instability, Exchange rate and consumer price index. In short run Gross Domestic Product (GDP), Political Instability (POI) and Population (POP) are the most significant determinants of FDI in Pakistan. The Error correction term shows that 21.11 % convergence in short run to long run within a year. This study concluded that Government should concentrate on the enhancement of growth rate and promote political stability in the country to bring the foreign investment inflow in the country.